2005
DOI: 10.1128/ec.4.4.639-648.2005
|View full text |Cite
|
Sign up to set email alerts
|

Surface Hydrophobicity Changes of Two Candida albicans Serotype B mnn4 Δ Mutants

Abstract: Cell surface hydrophobicity (CSH) of Candida species enhances virulence by promoting adhesion to host tissues. Biochemical analysis of yeast cell walls has demonstrated that the most significant differences between hydrophobic and hydrophilic yeasts are found in the acid-labile fraction of Candida albicans phosphomannoprotein, suggesting that this fraction is important in the regulation of the CSH phenotype. The acid-labile fraction of C. albicans is unique among fungi, in that it is composed of an extended po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 61 publications
1
34
0
1
Order By: Relevance
“…Various assays have suggested that deletion of YWP1 increases the surface hydrophobicity of yeast cells (unpublished observations), but efforts to reliably quantify this effect have been unsuccessful, in part because wild-type parental strain SC5314 is already relatively hydrophobic (38). Such an antihydrophobicity effect might be due to the abundance of Ywp1 if Ywp1 is indeed hydrophilic, but the mechanistic relationship between glycans, hydrophobicity, and adhesion remains complex and enigmatic at this time (38,55). Alternatively, the effect may be more specific.…”
Section: Discussionmentioning
confidence: 99%
“…Various assays have suggested that deletion of YWP1 increases the surface hydrophobicity of yeast cells (unpublished observations), but efforts to reliably quantify this effect have been unsuccessful, in part because wild-type parental strain SC5314 is already relatively hydrophobic (38). Such an antihydrophobicity effect might be due to the abundance of Ywp1 if Ywp1 is indeed hydrophilic, but the mechanistic relationship between glycans, hydrophobicity, and adhesion remains complex and enigmatic at this time (38,55). Alternatively, the effect may be more specific.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast suspensions were mixed with chloroform (volume relationship 5:1); the mixture was agitated for 1 minute and put to rest during 10 min at 37ºC. CSH was defined as the difference between absorbances at 520 nm of the aqueous phase before and after the confronting C. albicans suspension and the organic phase, ∆Abs (5).…”
Section: Determination Of Cell Surface Hydrophobicity (Csh)mentioning
confidence: 99%
“…The first stage of the infection includes adhesion to cellular surfaces. Adhesion of yeast has been studied using buccal epithelial cells, different cell lines, and plastic materials (3,4), with the cell surface hydrophobicity of fungus (CSH) as the main force implied in this process (5). Besides, C. albicans is capable of secreting exoenzymes, such as phospholipase (PL), and of developing hyphae, which allows penetration in oral tissues and, in turn, the infection process (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Attachment of C. albicans cells to materials is mediated by nonspecific interactions, such as hydrophobic and electrostatic forces, as well as by specific adhesin-ligand bonds (8,10,26,44,45,50). Cell hydrophobicity and charge also depend on cell growth morphology and cell surface structure (27).…”
mentioning
confidence: 99%